Effect of Oral Moxonidine and Oral Clonidine in the Attenuation of the Hemodynamic Responses Seen During Laparoscopic Cholecystectomy - A Comparative Study - Manjunatha S M; Khazi, Tohid Nazeer Ahmed; Triveni M R; Harsha Prakash B G (Academia Anesthesiologica International, 2022)
Background: Pneumoperitoneum created for laparoscopic surgeries result in various pathophysiological changes in the body especially on endocrine and cardiovascular system. Moxonidine, a newer drug acts selectively on imidazoline I1 receptor as agonist with weak ?2 agonist. Its site of action mainly in the rostral ventrolateral medulla (RVLM) in medulla oblongata, locus of CVS regulatory center situated. It reduces central sympathetic outflow causing the reduction in blood pressure and heart rate. Clonidine is a selective ?2 adrenergic agonist has beneficial effect of blunting hemodynamic responses due to intubation and pneumoperitoneum through its sympatholytic effects. This study compares the effect of oral Moxonidine versus oral Clonidine in attenuating hemodynamic responses to intubation and Pneumoperitoneum during laparoscopic cholecystectomy under general anaesthesia. Subjects and Methods: A total of 62 patients of ASA, PS I&II in the age group of 20-60 years of either sex scheduled for elective laparoscopic cholecystectomy were chosen for this prospective randomized double blind comparative study. They were randomly allocated to 2 groups, The Moxonidine (M) Group and The Clonidine (C) Group. Moxonidine Group receives Tab Moxonidine 0.2mg, 1 hour before induction and clonidine Group receives Tab clonidine 100mcg 1 hour before induction. Measurements: Heart Rate (HR), Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Mean Arterial Pressure (MAP), Oxygen Saturation (SpO2) measured at the points of preoperative (baseline), at induction, after induction, after intubation, before pneumoperitoneum, 5, 10, 20, 30, 40, 50, 60 minutes after pneumoperitoneum, after end of pneumoperitoneum and after extubation. Results: The comparison of vital parameters (HR, SBP, DBP, MAP) showed, significant reduction in HR, SBP, DBP, MAP in both groups (raise was not more than 20% from baseline) after intubation and pneumoperitoneum without any significant side effects. Clonidine caused reduction in SBP, DBP, MAP compared to Moxonidine (p<0.05), which was statically significant. But difference in HR among two groups was not statistically significant. There was no complication noted in the study. Both the drugs were found to be safe. Thus we found that clonidine premedication is better drug for lap cholecystectomy than Moxonidine. Conclusion: The Study drugs Moxonidine and clonidine as premedication, found to bring perioperative hemodynamic stability in ASA 1&2 patients, during pneumoperitoneum. And Clonidine is more effective drug than Moxonidine in maintaining stable hemodynamics during pneumoperitoneum in laparoscopic cholecystectomy.